Permasalahan Pengelolaan Keuangan Desa Ditinjau dari Perencanaan, Pelaksanaan, Penatausahaan, Pelaporan, serta Pertanggungjawaban - Amanda Yulia Damayanti; Annisa Nur Afifah; Herlina Manurung (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Local finance is all the rights and obligations of a village that can be valued in terms of money, as well as everything in the form of money or goods that a village can possess, related to implementation and obligations. Studies conducted on village finance management show various problems and constraints in each village. The method used in this research is Systematic Literature Review or SLR. Some of the constraints in village finance management include the low skills of human resources, lack of supervision and leadership, and a lack of understanding of applicable regulations. There are also villages that have successfully managed their finances well. Research shows that the role of village officials and a good understanding of regulations and procedures for village finance management are important factors in the success of village finance management. Therefore, it is expected that the management of village finance can be more effective and efficient, and contribute to economic growth and regional stability.